Adsorption properties of graphite oxide for Rhodamine B. (25th September 2019) - Yin, Minyuan; Pan, Yusong; Pan, Chengling
Abstract : In the present study, the adsorption properties of graphite oxide (GO) for Rhodamine B (RhB) under different conditions was investigated. The specific surface area of the GO adsorbent decreased from 71.5 m 2 g −1 for before adsorption of RhB to 4.9 m 2 g −1 for after adsorption of RhB. The maximum adsorption capacity was 578.0 mg g −1 at 303.15 K. Moreover, the pH value has a great influence on the adsorption properties of GO. The adsorption capacity of GO for RhB increased first and then decreased with the rise of pH value. Study on the adsorption kinetics verified that the adsorption process conformed to the pseudo‐second‐order model adsorption process. The isothermal model is consistent with the Langmuir isothermal model and belongs to the monolayer chemical adsorption.